Optimisation of stable flight posture of ski jumping based on computational fluid dynamics simulation technology - Yu, J.; Liao, Z.; Ma, X.; Qi, S.; Liang, Z.; Wei, Z.; Zhang, S. (Sports Biomechanics, 2025)
The stable flight posture that affects sports performance during flight is usually formed by the multiple angles of the athlete—ski posture. At present, research on the flight phase is mainly based on the single-factor impact analysis based on computational fluid dynamics simulation technology, but studies on the multi-factor coupling relationship of two or more factors is less. This study aims to determine the best optimal-level combination based on the simulation model of this work through comprehensive evaluation from the optimisation perspective of multi-factor coupling. Here, a refined model of the athlete—ski system with the characteristics of ski jumping was established. Reynolds time-averaged method was used for the simulation. A three-factor and five-level simulation test was conducted on the relative inclination between skis, the angle between the body and the ski and the ski V-angle through orthogonal experiment design. Our results show that the optimal-level combination of the relative inclination between skis of 120°, the angle between the body and the ski of 20°, and the ski V-angle of 30° is relatively best in terms of aerodynamic characteristics. Simulation results were similar to the results of the winter field data from video analysis, and the results were effective.